A Message to Our 2024 Peer Reviewers: Thank You - Advocate Aurora Research Institute (Journal of Patient-Centered Research and Reviews)
Like all peer-reviewed journals, we rely heavily on our diverse pool of academic and clinical reviewers who generously volunteer their time to help rigorously gatekeep original manuscript submissions to the Journal of Patient-Centered Research and Reviews (JPCRR). Indeed, the high-quality science and patient-centered focus of our published articles are a testament to the hard work that these scholarly reviewers devote to the journal. Listed in this citable acknowledgment are the names of each of our peer reviewers from the past 12 months, and we sincerely thank them for their valuable contributions to JPCRR and our goal of advancing patient-centered practices, health outcomes, and patient experiences.